2016
DOI: 10.21037/jtd.2016.02.67
|View full text |Cite
|
Sign up to set email alerts
|

Robot-assisted coronary artery bypass grafting improves short-term outcomes compared with minimally invasive direct coronary artery bypass grafting

Abstract: RACAB may be a valuable alternative for patients requiring single or simple multi-vessel coronary artery bypass grafting (CABG). Although the mid-term mortality outcomes are similar, RACAB improves short-term outcomes and mid-term MACCE-free survival compared with MIDCAB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 23 publications
3
40
0
Order By: Relevance
“…RA-MIDCAB entails a shorter intubation time and a shorter stay at post-operative care units, with more patients transferred post-operatively to the PACU (fast-track treatment). These findings are in line with previous studies [26,27]. Hospital length of stay (LOS), however, showed no significant difference between the two study groups.…”
Section: Comparison Of Minimally Invasive and Conventional Coronary Asupporting
confidence: 92%
“…RA-MIDCAB entails a shorter intubation time and a shorter stay at post-operative care units, with more patients transferred post-operatively to the PACU (fast-track treatment). These findings are in line with previous studies [26,27]. Hospital length of stay (LOS), however, showed no significant difference between the two study groups.…”
Section: Comparison Of Minimally Invasive and Conventional Coronary Asupporting
confidence: 92%
“…Of these, 13 were included in the review. [7][8][9][10][11][12][13][14][15][16][17][18][19] Detailed descriptions of included and excluded studies can be found in Appendix 1.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies were based on national databases, 10,11 and the remaining 11 studies were singlecentre. [7][8][9][12][13][14][15][16][17][18][19] Patients were selected between 1998 and 2014, and sample sizes ranged from 38 to 966 211. Seven studies compared RCAB to C-CABG, on or off pump, 7,[12][13][14][15][16][17] 3 studies compared RCAB to MIDCAB, [17][18][19] and 1 study compared RCAB to PA-CAB.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Less invasive cardiac surgery describes a group of alternative incisions or techniques that aim to reduce the surgical trauma, potential complications and burden of slow recovery following heart surgery. It is widely utilised in advanced centres in the West, China, Korea and Japan, (2)(3)(4)(5)(6) and facilitates and encompasses procedures on heart valves, coronary arteries, arrhythmias and heart failure in various permutations. The most sublime and advanced forms of less invasive cardiac surgery can be said to be hybrid procedures, which are executed by heart surgeons and cardiologists together or in sequence.…”
Section: Introductionmentioning
confidence: 99%